Strategi Kepemimpinan Kepala Sekolah Dalam Pengembangan Kompetensi Sosial Guru Dengan Kerjasama Masyarakat Melalui Budaya Bobaso Se Rasai - Irsan Habsyi (Peneliti.net, 2022)
This study aims to find out about local cultural values ​​as a reference by the government in this case, the Directorate of National Education Office of the Republic of Indonesia so that it becomes an understanding of schools in Indonesia and provides opportunities to better know and understand local cultural values ​​wisely and effectively. wise to practice in school. Furthermore, this study describes the principal's leadership strategy in developing teacher social competence with community cooperation through the bobaso serasai culture. The research used descriptive qualitative research and the research design was a multi-case study. Data was collected through in-depth interviews, observation, and documentation studies as research objectives. Researchers used snowball data analysis. Data validity was carried out for credibility, transferability, dependability and confirmability. The results showed that the social competence of teachers as the main actors in schools needed the support of community cooperation which became a strength for school principals to learn the cultural values ​​of bobaso as felt in the community. This research was conducted in 2019, at SMA Negeri 1 Ternate City, SMK Negeri 1 Ternate City and Madrasah Aliyah Negeri 1 Ternate City, North Maluku Province-Indonesia. As a research, namely prioritizing bobaso cultural values ​​according to the people of Ternate City as local wisdom to implement teacher social competence in schools effectively. In addition, the bobaso cultural dimension seems to be very dominant in supporting the principal's program in teacher-community collaboration